2021
DOI: 10.3389/fpubh.2021.688300
|View full text |Cite
|
Sign up to set email alerts
|

Health-Promoting Behaviors, Risk Perceptions, and Attention to COVID-19-Related Information: Comparing People's Responses to the COVID-19 Pandemic Across Times of Chinese New Year and Summer 2020 in Hong Kong

Abstract: Background: Since the start of the COVID-19 pandemic, individuals have been encouraged to engage in health-promoting behaviors, namely actions taken to prevent infection and keep themselves healthy, such as maintaining social distancing. However, other factors, such as risk perception and feelings of fear, also might influence whether an individual takes such measures. This study compared people's responses to the pandemic in terms of their adoption of COVID-19 health-promoting behaviors, COVID-19 risk percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Previous COVID-19 studies conducted in Hong Kong only focused on relevant concepts such as risk perception, preventive behaviors, and vaccination hesitancy [ 18 , 19 ], rather than perceived harms and benefits as we did. A previous qualitative study during the SARS pandemic in Hong Kong identified three subgroups of perceived harms and benefits, including the cost (harm), benefit, and mixed (ambivalent) subgroups [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous COVID-19 studies conducted in Hong Kong only focused on relevant concepts such as risk perception, preventive behaviors, and vaccination hesitancy [ 18 , 19 ], rather than perceived harms and benefits as we did. A previous qualitative study during the SARS pandemic in Hong Kong identified three subgroups of perceived harms and benefits, including the cost (harm), benefit, and mixed (ambivalent) subgroups [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…We designed a research model based on the theoretical basis that positive health behaviors could influence other healthy behaviors [ 15 , 16 ]. Positive health behavior is a lifestyle wherein a person predicts health risks and actively responds to such risks.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the unhealthy effects and negative social perceptions that can result from not practicing NPIs during the COVID-19 pandemic situation can affect an individual’s participation in preventive behavior [ 14 ]. A health promotion behavior is an action that a person practices to manage health and prevent infection, and practicing health promotion behavior can strengthen the immune system and reduce negative impacts on health [ 15 ]. Therefore, we need to determine whether social distancing can also be considered a health-promoting action.…”
Section: Introductionmentioning
confidence: 99%